Long-lasting effect of obesity on skeletal muscle transcriptome - Ilhem Messaoudi; Mithila Handu; Maham Rais; Suhas Sureshchandra; Byung S. Park; Suzanne S. Fei; Hollis Wright; Ashley E. White; Ruhee Jain; Judy L. Cameron; Kerri M. Winters-Stone; Oleg Varlamov (BMC Genomics, 2017)
Abstract Background Reduced physical activity and increased intake of calorically-dense diets are the main risk factors for obesity, glucose intolerance, and type 2 diabetes. Chronic overnutrition and hyperglycemia can alter gene expression, contributing to long-term obesity complications. While caloric restriction can reduce obesity and glucose intolerance, it is currently unknown whether it can effectively reprogram transcriptome to a pre-obesity level. The present study addressed this question by the preliminary examination of the transcriptional dynamics in skeletal muscle after exposure to overnutrition and following caloric restriction. Results Six male rhesus macaques of 12–13 years of age consumed a high-fat western-style diet for 6 months and then were calorically restricted for 4 months without exercise. Skeletal muscle biopsies were subjected to longitudinal gene expression analysis using next-generation whole-genome RNA sequencing. In spite of significant weight loss and normalized insulin sensitivity, the majority of WSD-induced (n = 457) and WSD-suppressed (n = 47) genes remained significantly dysregulated after caloric restriction (FDR ≤0.05). The MetacoreTM pathway analysis reveals that western-style diet induced the sustained activation of the transforming growth factor-β gene network, associated with extracellular matrix remodeling, and the downregulation of genes involved in muscle structure development and nutritional processes. Conclusions Western-style diet, in the absence of exercise, induced skeletal muscle transcriptional programing, which persisted even after insulin resistance and glucose intolerance were completely reversed with caloric restriction.